Repeated electroconvulsive shock does not increase the susceptibility of rats to a cage convulsant (isopropylbicyclophosphate). - Cowen, P; Nutt, D; Green, A (1980)
Intravenous infusion of isopropylbicyclophosphate (IPTBO), a cage convulsant, produced a seizure which was qualitatively very similar to that seen after picrotoxin administration, but with a shorter latency. Pretreatment of rats with either a single electroconvulsive shock (ECS) or a single ECS daily for 10 days did not alter the dose of IPTBO necessary to elicit a seizure 24 h after the final ECS. This data together with other previously published work argues against repeated ECS altering seizure susceptibility in rats.